Insights into the genomic architecture of a newly discovered endophytic Fusarium species belonging to the Fusarium concolor complex from India - Rana, Shiwali; Singh, Sanjay K. (Frontiers in Microbiology, 2023)
In this paper, a new species Fusarium indicum belonging to Fusarium concolor species complex is established to accommodate an endophytic fungus isolated from Bambusa sp. collected from Himachal Pradesh. The identity of this isolate was confirmed based on the asexual-morphs, its cultural characteristics as well as phylogenetic analyses. This isolate was revealed to be distinct by showing less similarity with described species based on molecular sequence data; nearly 93.9% similarity based on translation elongation factor 1-alpha, and 94.2% similarity based on RNA polymerase II subunit. Further, to increase knowledge about this novel species, whole-genome sequencing was carried out. The results displayed that Fusarium indicum NFCCI 5145 possesses a total of 40.2 Mb genome and 48.39% GC content. About 12,963 functional protein-coding genes were carefully predicted and annotated using different BLAST databases, like Uniprot, Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Ontology (GO), Pathogen Host Interactions (PHI), Clusters of Orthologous Groups (COG), and Carbohydrate-Active enzymes (CAZy) databases. The orthologous proteins were identified using OrthoFinder and used for the phylogenetic analysis. ANIb too confirmed that the isolate is closely related to F. concolor species complex. It is known that Fusarium strains can produce a wide range of bioactive secondary metabolites. Therefore, in-depth mining for biosynthetic gene clusters for secondary metabolites biosynthesis of Fusarium indicum NFCCI 5145 was investigated using Antibiotics and Secondary Metabolites Analysis Shell (AntiSMASH) annotation. AntiSMASH results displayed that this isolate possesses 45 secondary metabolites biosynthetic gene clusters (BGCs). These findings significantly improved our understanding of the strain Fusarium indicum NFCCI 5145 and its possible applications in different sectors including industry for the secondary metabolites and enzymes it can produce.